การผลิตโฟมอะลูมิเนียมที่ทำให้เสถียรด้วยขี้เถ้าแกลบ - รัฐ ตันติศิริไพบูลย์ (จุฬาลงกรณ์มหาวิทยาลัย, 2008)
The objective of this work is to study the effects of rice husk ash (RHA) on the expansion, structure and mechanical properties of Al foams. The RHA was separated to four different sizes. Its contents added in Al foams were varied in the range of 1 – 3 wt.%. Al foams were produced through a powder metallurgical route at 800℃. The RHA was produced by the chemical treatment using HCl or H₂SO₄, followed by the heat in a furnace at 700℃ for 3 h, using a heating rate of 5℃/min. The sectioned foam samples with the length of 30 mm were compressed at the cross head speed of 5 mm/min to 60% strain.It is found that the addition of RHA, in all cases, resulted in a decrease in the foam expansion, compared with the pure Al foam. The expansion decreases more when RHA with smaller size was added. The expansion also decreases when more amounts of RHA were added. However, better uniform foam structure was obtained when RHA, in all cases, was added. The addition of RHA resulted in an increase in the cell wall thickness. The compressive strength and energy absorption of Al foams increase when RHA has smaller size and more amounts of RHA were added.